The Effect of Profitability, Company Size, and Liquidity on Financial Performance of Healthcare Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2019-2023 - Afrianda Zulham; Ina Liswanty; Emi Masyitah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Financial performance gives an overview of how well a firm is able to fulfill its obligations in terms of properly managing financial aspects by reflecting its financial state over a specific time period. Financial performance can be impacted by variables like liquidity, company size, and profitability. With a population of all health sector companies listed on the IDX, this study employs a quantitative methodology. Purposive sampling is used in the sample research approach, and 10 companies make up the sample size. With the aid of SPSS software version 27, data analysis was done using multiple linear regression and descriptive statistics. The study's findings suggest that: (1) Financial performance is positively and significantly impacted by profitability; (2) company size has no discernible impact on financial performance; (3) financial performance is significantly positively impacted by liquidity; and (4) the financial performance of health sector companies is significantly impacted favorably by profitability, company size, and liquidity all at once.